Changes in prevalence, awareness, treatment and control of hypertension in Thai population, 2004-2009: Thai National Health Examination Survey III-IV - Wichai Aekplakorn (2018)
Objective: To determine the changes in prevalence, awareness, treatment and control of hypertension and their metabolic risk factors in Thai population between 2004 and 2009. Methods: The Thai National Health Examination Survey (NHES) in 2004 and 2009 data were used. Blood pressure and anthropometric measurements were performed. Prevalence, awareness, treatment and control of hypertension of Thai population aged at least 15 years were calculated. Analyses were weighted to the probability of sampling. Results: The prevalence of hypertension in 2004 and 2009 were relatively stable at approximately 21.0%. There was improvement in awareness of hypertension, from 18.2% for men and 33.0% for women in 2004 to 39.5 and 59.4% in 2009, respectively. The high blood pressure control rates improved from 4.8 to 14.4% for men and from 10.8 to 27.2% for women, respectively (all P<0.05). The improvement in awareness, treatment and control of hypertension was also observed in individuals with diabetes, obesity and hypercholesterolemia. However, among hypertensive individuals, there were increases in proportions of obesity (BMI ≥ 25kg/m) between two surveys: from 39.1 to 47.5% in men and from 54.6 to 62.9% in women, respectively (all P<0.05). CONCLUSION:: Despite improvement in awareness and control of hypertension in Thai population, a large proportion of hypertensive individuals remained suboptimally controlled. Strengthening measures to control high blood pressure and metabolic risk factors, especially obesity and hypercholesterolemia, in individuals with hypertension are needed. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.